Most elite athletes return to competition following operative management of meniscal tears: a systematic review. Issue 2 (23rd January 2018) - Ekhtiari, Seper; Khan, Moin; Kirsch, Jacob M; Thornley, Patrick; Larson, Christopher M; Bedi, Asheesh
Abstract : Importance: Meniscal injuries are common among athletes. When operative management is indicated, the decision between meniscal repair and meniscectomy is not always clear, particularly in elite athletes. Objective: The aim of this systematic review was to (1) compare outcomes for partial meniscectomy and repair for the management of meniscus tears in elite athletes and (2) describe return-to-play (RTP) rates and complications for each operation. Evidence review: MEDLINE, Embase and PubMed were searched from inception through to 5 March 2017. All studies were screened in duplicate for eligibility. Data extracted included demographics, surgical technique and RTP rate and timeline. Findings: Ten studies (725 athletes) were included involving 355 elite athletes undergoing meniscal repair (111 patients) or partial/total meniscectomy (244). The majority of athletes were men (82.8%) and had a mean age of 25.0 years (14–38). Athletes were followed for a mean of 5.3 years (range=3 months to 18.4 years). American football was the most common sport (153 athletes), followed by soccer (69) and basketball (67). Athletes undergoing meniscal repair demonstrated a pooled mean RTP time of 7.6 months in comparison to 4.3 months for those undergoing partial meniscectomy (P<0.0001). Of athletes undergoing meniscal repair, 86.5% RTP at their preoperative level, compared with 80.4% of athletes undergoing partial meniscectomy (P=0.24). Following meniscectomy, athletes who were taller, drafted in higher rounds and had played or started more games preoperatively were less likely to suffer negative career impacts postoperatively. Satisfaction rates (92% vs 76%) and clinical scores (8.8 vs 6.9, P=0.05) were higher among recreational than elite athletes. Conclusion: Athletes undergoing partial meniscectomy RTP sooner than those undergoing meniscal repair. Both operations are safe and the majority of athletes RTP at their preoperative level of competition following either operation. Further research is required to identify when each option is preferable in this population. Relevance: Based on the currently available evidence, meniscectomy and meniscal repair are both viable options for elite athletes with meniscal injuries. Each method has small advantages and disadvantages compared with the other, and thus a shared decision should be made with the athlete. Level of evidence: Level IV, systematic review of level III and IV studies.